Pengembangan Tilawatil Quran Remaja Berbasis Manajemen Dakwah Di Kelurahan Marindal II - Rojas Mulia Akbar; Sahrul Sahrul (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study aims to determine the development of adolescent Quran recitation based on da'wah management in Marindal II Village, Patumbak District, Deli Serdang Regency. The research method used was qualitative with a descriptive approach. Data were obtained through interviews, observations, and documentation with one of the administrators of the Quran recitation group. Using the da'wah management approach, adolescent Quran recitation skills can be developed in a more structured and effective manner. This paper discusses strategies, models, and programs for effective Quran recitation development for adolescents. The results show that the da'wah management approach can significantly improve adolescent Quran recitation skills. This paper is also expected to serve as a reference for educators, preachers, and da'wah practitioners in developing Quran recitation skills.